Clinically relevant haemolysis after transcatheter aortic valve implantation with new-generation balloon-expandable valve - Mitsuaki Isobe; Mitsunobu Kitamura; Mamoru Nanasato; Itaru Takamisawa; Ryosuke Higuchi; Makoto Ohno (Open Heart)
Background Valve-related haemolysis is a known complication following prosthetic valve surgery. Haemolysis after transcatheter aortic valve implantation (TAVI) has been reported in some studies, all of which were non-critical. Data related to haemolysis associated with new-generation balloon-expandable valve (BEV) are scarce.Methods Among 441 patients who underwent TAVI between April 2023 and June 2024, 282 patients treated with new-generation BEV were analysed. Haemolysis was defined based on the lactate dehydrogenase, haemoglobin, reticulocyte and haptoglobin levels. Clinically relevant haemolysis was defined as a case requiring transfusion and/or reintervention.Results Clinically relevant haemolysis occurred in 6 of 282 patients (2.1%), with median age of 84 years. Three (50%) received a 20 mm valve, and the oversizing ranged from −6.6% to +2.7%. All patients (100%) exhibited paravalvular leakage at the native commissural sites, with moderate or greater paravalvular leakage in two (33%). Lactate dehydrogenase levels exceeded 1200 IU/L in five (83%), four (67%) required transfusion and three (50%) underwent reintervention: balloon aortic valvuloplasty in one and valve-in-valve procedures in two. Haemolysis regressed in three reintervention cases; however, one patient died 9 days postoperatively due to COVID-19. Among three patients (50%) managed conservatively, one developed prosthetic valve endocarditis, whereas another showed spontaneous regression of haemolysis. Over a median follow-up of 218 days, five patients (83%) survived.Conclusion Clinically relevant haemolysis occurred in 2.1% of patients undergoing TAVI with new-generation BEV, with 67% requiring transfusion and 50% undergoing reintervention. Further research is warranted to identify risk factors and optimise management strategies for haemolysis.